?ULTRAVIOLET AND VISIBLE ABSORPTION AND SPECTRAL SHIFTS OF SOME SCHIFF BASES DERIVED FROM N, -ETHYLENEDIAMINE - TAHER, M. A. EL-; GABR, A. A. (Biological Sciences - PJSIR, 1994)
The electronic absorption spectra of the Schiff bases, in the present not [N,N-di(X-bCnzylidenes) ethylenediamine], have been investigated inorganic solvents of different polarities. The main visible band observed in all of the compounds examined, in ethanol, is assigned to the electronic transitions within the whole molecule of such compounds as an intra- molecular charge transfer (CT) interaction. The position ofthis band is quite sensitive to nature of substituent X. On the other hand, an additional visible band appeared in each of compound II (X=Q-OH) and compound IV (X=N (CH3)2)’ This can be attributed to an intermolecular CT transition in case of the former compound and to high stabilization of the polar excited state of later compound by an ethanol molecule. Furthermore, the pKa values of the substituent X, have been determined and related to the geometric flexibility of such compounds.